Remote home: uma plataforma para interações via dispositivos móveis em ambientes residenciais - GOMES, Fábio Fonseca Barbosa (2016)
Nowadays, society is increasingly dependent on an integrated and enhanced technology to the needs of their daily lives. Mobile devices have gained popularity and usually the individuals carry with them. Thus, they become a computational vehicle in various applicability. Thus, the main objective of this paper is to present a platform that allows user interaction with different electronic devices through a universal remote control, implemented in a smartphone application. To achieve the expected results, a literature search was conducted in order to verify the papers on universal remote control for home environments this search. After a model was developed in three layers, with the purpose of structuring the architecture to integrate commands executed from a smartphone with electronic devices available in an interactive setting. To validate the model, a platform covering the mobile application (universal remote) was built, a middleware (communication infrastructure) and actuators (electronic devices). To check the platform capabilities and application usability, an experiment was conducted with the participation of 30 people who responded to a questionnaire in order to contribute to the evaluation of the proposal. One of the potential contribution of this work is to have the ability to control and identify the electronic devices in the environment, including those that do not have a remote control, and increase the quality of life of people, especially those with mobility restrictions. The results suggest that the solution is valid and works satisfactorily in residential environments.